US Anti-Trafficking Funding and the Discourse of ‘Prevention’ - Hebert, Laura (Anti-Trafficking Review, 2024)
The United States government has positioned itself as the global exemplar in the anti-human trafficking arena, including through its unparalleled financial support for domestic and international anti-trafficking activities. How the US has allocated these funds has not previously been systematically studied. Building on original databases compiled through a review of the US Attorney General’s Annual Report to Congress on US Government Activities to Combat Trafficking in Persons for fiscal years 2017–2021, in this article, I offer a detailed analysis of US anti-trafficking funding allocations. I find that during the five-year period under review, the vast majority of US anti-trafficking funds were spent on reactive activities, including the identification, protection, and support of trafficking survivors and efforts to improve the detection, arrest, and prosecution of traffickers. In contrast, activities targeting the conditions that increase precarity, rendering certain populations at heightened risk of being trafficked, or that enable the exploitation of precarity, were relatively under-funded. When these conditions were addressed by funded activities, the targets were nearly always countries in Africa, Asia, or Latin America, perpetuating a discourse of trafficking as a social problem rooted in poor policies, practices, and inequalities seen as endemic in the Global South.